PECULIARITIES OF ORGANIZING VOCATIONAL TRAINING OF SKILLED WORKERS IN THE CONDITIONS OF BLENDED LEARNING - Kruchek, Viktoriia (Professional Pedagogics, 2022)
The study relevance of vocational training organization of skilled workers in the conditions of blended learning is determined by the need to quickly adapt the system of vocational (vocational and technical) education to changes in various spheres of public life, in particular, globalization, integration into the European space, digitalization, quarantine restrictions, military operations in Ukraine for the effective implementation of educational tasks.Goal: to analyse the state and peculiarities of the organization of vocational training of skilled workers in the conditions of blended learning.Methods: analysis of philosophical, general scientific, methodical, psychological and pedagogical literature and generalization of its results – to identify the state of development of the problem; survey – to study the state of organization of vocational training in blended learning; comparison – to compare empirical data.Results: the article analyzes the state and peculiarities of vocational training organization of skilled workers in the conditions of blended learning.Conclusions: it is found that there is a need for state regulation and definition of the blended learning status, unification and efforts coordination of teachers, methodologists, scientists in the field of digitalization of education, creation and use of digital educational tools, digital competence development of teachers and students, dissemination of positive domestic and international pedagogical experience in the use of digital technologies through open specialized electronic platforms. Pedagogical staff are sufficiently motivated to master digital educational tools and technologies for organizing blended learning, are aware of the need to improve the level of digital culture. The most popular forms of professional development in this area are interactive forms that involve subject-subject interaction and partnership. There is a need to update the educational standard, vocational teacher training programs, and the content of teacher training programs; create an appropriate information and educational environment; and promote the practice of holding master classes, trainings, and webinars on the use of digital technologies to improve the digital competence of teachers.
Keywords: blended learning; online learning; distance learning; digital competence; digitalization of education